Monitoring Cerebral and Renal Oxygenation Status during Neonatal Digestive Surgeries Using Near Infrared Spectroscopy - Beck, Jonathan; Loron, Gauthier; Masson, Claire; Poli-Merol, Marie-Laurence; Guyot, Eliane; Guillot, Camille; Bednarek, Nathalie; François, Caroline (Frontiers in Pediatrics, 2017)
Background Depending on the initial pathology, hypovolemia, intra-abdominal hypertension, and sepsis are often encountered in neonatal digestive surgery. Accurate newborn monitoring during and after surgery is essential to adapt resuscitation protocols. Near infrared spectroscopy (NIRS) is non-invasive and can detect hypoperfusion which indicates a low circulatory blood flow, regardless of the cause. Objective Evaluating changes in cerebral and renal regional oxygen saturation during neonatal digestive surgeries, conducted according to normal practices, with commonly used monitoring parameters. Analyzing retrospectively the inter-relationships between NIRS values and mean arterial pressure (MAP) values as well as pre-ductal SpO2. Methods Prospective, descriptive, monocentric study. All neonates referred for surgery were included. NIRS allows the measurement of cerebral and renal oxygenation fluctuations, as well as calculating difference in intraoperative and postoperative values. Results Nineteen patients were included. Cerebral regional oxygen saturation (C rSO2) values were stable while renal regional oxygen saturation (R rSO2) values tended to decrease with time during surgery. Indeed, 72% of rSO2 decline episodes occurred after the first 30 min of surgery, without any significant statistical differences for the next 90 min of surgery. After surgery, the lowest average C and R rSO2 values were evidenced during the first 6 h, with 60% of C rSO2 and R rSO2 anomalies occurring in that time frame. There was no significant statistical difference observed in the following 18 h. There was a significant correlation between R rSO2 and SpO2 values (p < 0.01), but not with C rSO2 values. There was no correlation with the MAP either for the C rSO2 values or R rSO2 ones. Conclusion NIRS is a promising non-invasive bedside tool to monitor cerebral and tissue perfusion, analyzing tissue microcirculation. NIRS has its interest to guide neonatal digestive surgeries (bowel manipulation, viscera reduction) and may represent an early warning for identifying patients requiring resuscitation during or after these surgeries.